Determinants of survival of extremely low birth weight infants in a rural Nigerian Hospital - Babatunde, O Kayode-Adedeji; Sylvester, O Alikah; Irene, E Akhige (Indian Journal of Child Health, 2015)
Background: Over 90% of the neonatal deaths occur in low- and middle-income countries, mostly in sub-Saharan Africa, including Nigeria. Prematurity is related to more than one-third of these deaths on a global scale; with the extremely low birth weight (ELBW) category having a 100-fold mortality risk compared to the normal birth weight infants. Objective: The purpose of this study was to determine the survival rates of ELBW infants and to identify the factors associated with survival in a rural hospital in Nigeria. Materials and Methods: All the neonates admitted to the unit weighing